Analysis of the Physicochemical Characteristics of the Soil in the Malakand District, Khyber Pakhtunkhwa, Pakistan - Ibrahim, Muhammad; Akhtar, Naveed; Haq, Aminul; Sara,; Sadaf,; Mohsin Ullah, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
The aim of the present study was to assess the physicochemical characteristics of the soil of 20 selected sites in the district of Malakand, Pakistan. The study showed that the soil texture of District Malakand was predominantly sandy loam (50%) to silty loam (25%) and loamy sand (25%). The pH value of the soil ranged from 6.7 to 8.2. The electrical conductivity of soil samples ranged from 0.201 dS/m to 0.683 dS/m. The organic matter content has a range of 0.70% to 2.27%. In the macronutrients, the Nitrogen content was found in the range of 300 ppm to 1500 ppm, Potassium from 28 ppm to 190 ppm, Phosphorus from 6.2 ppm to 14.4 ppm, Calcium element from 2.18 ppm to 7.75 ppm, Magnesium from 3.24 ppm to 6.09 ppm and Sodium from 12.21 ppm to 18.29 ppm. Similarly, microelements such as Zinc ranged from 1.37 ppm to 2.22 ppm and Manganese from 0.53 ppm to 1.63 ppm. The results showed a significant Positive Pearson's correlation coefficient, with the highest correlation were observed between Pb-Na (r = 0.803), followed by P-N (r = 0.759) and N-EC (r = 0.677); whereas, a significant negative Pearson's correlation coefficient were found for Ca-K (r = -0.579), Mg-K (r = -0.467) and Ni-P (r = -0.454). The probability values show a significant correlation (p <0.01* and p <0.05**) between pH and Ec (0.023**), Ca-K (0.003*), N-Mg (0.041**), K-Mg (0.018**), Zn-Ca (0.038**), and Zn-Mg (0.046**). This study provides valuable insights into the physicochemical characteristics of soil in Malakand Distrcit, contributing to a better understanding of soil health and its implications for agriculture and environmental sustainability.